Effects of Midface Hypoplasia and Facial Hypotonia at Rest and During Clenching on Drooling in Down syndrome Children - Wijaya, Ilice Collins; Yohana, Winny; Chemiawan, Eka; Saptarini, Risti; Irmaleni, Irmaleni; Nuraeni, Nanan; Soewondo, Willyanti (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Down syndrome is a chromosome 21 disorder and the most common cause of physical abnormalities including midface hypoplasia, facial hypotonia, and also drooling. Drooling is unintentional anterior salivary flow from the mouth. The objectives of the study is to determine and analyze the effects of midfacial hypoplasia and facial hypotonia on drooling in Down syndrome children. Subject and method: METHODS: of the research is analytic correlational. Sample retrievement using purposive sampling technique and obtained 20 samples that fulfills the inclusive criterias, consisting of 13 boys and 7 girls with an age range of 6 to 16 years old. RESULTS AND DISCUSSION: The results were tested statistically by Kendall Coefficient of Concordance Test and Spearman Coefficient of Rank Correlation Test. The results showed that the effect of midfacial hypoplasia, facial hypotonia at rest, and during clenching on drooling is very significant (p-value 0.0002) with Kendall Coefficient of Concordance. Spearman Coefficient of Rank Correlation test results show correlation of midface hypoplasia on drooling is not significant (p-value 0,1265). Facial hypotonia at rest has a very significant correlation on drooling (p-value 0,0000) and during clenching also has a very significant correlation (p-value 0,0000). CONCLUSION: Conclusion of the research is there are effects of midface hypoplasia, facial hypotonia at rest and facial hypotonia during clenching on drooling, also facial hypotonia at rest and facial hypotonia during clenching on drooling, but no effect of midface hypoplasia on drooling in Down syndrome children.